How to develop a battery-electric propulsion concept for a vessel? - De la Fuente Manríquez, Jorge (Revista de Marina, 2025)
Nowadays, maritime transport is experiencing the beginning of a transition towards less polluting propulsion systems, such as electricity, which can be obtained with the use of batteries. The following example presents, in summary, how a motorization could be developed under the concept of electric batteries for a zero GHG emission ship that makes short-distance trips with an electrical supply in port.